Prototype of IoT-Enabled RFID Door Lock System Using n8n Workflow Integration - Ilmawan Mustaqim; Dzul Fadli Rahman; Heri Nurdiyanto; Abdul Khaliq Pangestu; Fauzi Wijaya (Universitas Dharma Wacana, 2026)
This study aims to develop a Radio Frequency Identification (RFID)-based door lock system integrated with the n8n automation platform as an innovative solution to enhance access security within an academic envi-ronment. The research employs a Research and Development (R&D) method with a Waterfall Model approach, consisting of requirement analysis, system design, hardware and software implementation, and prototype test-ing stages. The system utilizes an RFID RC522 module, an ESP8266 microcontroller, an I2C LCD, and a 12V Li-Ion battery, integrated through an n8n workflow to automatically record access data into an Excel data-base. The test results show that the system can perform user authentication and real-time access logging with 100% accuracy and an average response time of five seconds. The casing, printed using a 3D printer with PLA filament, provides a lightweight, durable, and easily assembled design. Overall, the developed system functions effectively as both a control and monitoring tool, demonstrating potential as a model for smart security system development in higher education institutions